2021
DOI: 10.3389/fsufs.2021.620426
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Compositions of Edamame Genotypes Grown in Different Locations in the US

Abstract: The consumption of edamame [Glycine max (L.) Merr.] in the US has rapidly increased due to its nutritional value and potential health benefits. In this study, 10 edamame genotypes were planted in duplicates in three different locations in the US—Whitethorne, Virginia (VA), Little Rock, Arkansas (AR), and Painter, VA. Edamame samples were harvested at the R6 stage of the bean development when beans filled 80–90% of the pod cavity. Afterward, comprehensive chemical composition analysis, including sugars, alanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…In addition, edamame is a rich source of vitamins A, B1, B2, vitamins C (ascorbic acid), vitamin E (tocopherol), niacin, and healthpromoting polyunsaturated fatty acids, such as linoleic acid and linolenic acid [18,19]. Edamame also contains a significant amount of dietary fiber, which when consumed in sufficient quantities could help to reduce blood cholesterol levels due to its viscosity, solubility, and ability to bind molecules [20].…”
Section: Nutritional and Functional Valuesmentioning
confidence: 99%
“…In addition, edamame is a rich source of vitamins A, B1, B2, vitamins C (ascorbic acid), vitamin E (tocopherol), niacin, and healthpromoting polyunsaturated fatty acids, such as linoleic acid and linolenic acid [18,19]. Edamame also contains a significant amount of dietary fiber, which when consumed in sufficient quantities could help to reduce blood cholesterol levels due to its viscosity, solubility, and ability to bind molecules [20].…”
Section: Nutritional and Functional Valuesmentioning
confidence: 99%
“…Edamame taste is directly associated with its nutritional and chemical profiles, and edamame taste scores were reported to be positively related to sucrose, alanine, glutamic acid, and aspartic acid contents . In general, edamame sweetness is associated with a sugar profile, the umami/savory taste with amino acids content, and sourness and bitterness with the presence of saponins and isoflavones. Several free sugars (fructose, glucose, glucarate, galactarate, galactose, maltose, and mannose) have been identified and quantified in edamame, but sucrose is the main component that contributes to its desired sweet taste and corresponds to 78.9% to 93.7% of its total sugar content . In fact, Yu et al reported a strong correlation between sucrose content and total sweetness of edamame ( r = 0.94).…”
Section: Role Of the Basic Tastes In Edamame Flavormentioning
confidence: 99%
“…In general, edamame sweetness is associated with a sugar profile, the umami/savory taste with amino acids content, and sourness and bitterness with the presence of saponins and isoflavones. Several free sugars (fructose, glucose, glucarate, galactarate, galactose, maltose, and mannose) have been identified and quantified in edamame, but sucrose is the main component that contributes to its desired sweet taste and corresponds to 78.9% to 93.7% of its total sugar content . In fact, Yu et al reported a strong correlation between sucrose content and total sweetness of edamame ( r = 0.94). Nevertheless, the relationship between edamame total sugar and individual sugars is not simple and seems to vary in different studies, which may make breeding selection for these traits difficult …”
Section: Role Of the Basic Tastes In Edamame Flavormentioning
confidence: 99%
See 2 more Smart Citations